Pasta de gesso com incorporação de resíduo de gesso e aditivo retardador de pega - Trovão, Ana Paula Milagres (2012)
The use of plaster in civil construction generates a large amount of waste, but it is a material that posses properties that makes it a highly competitive product. The main cause of the generation of this waste is the rapid hardening of the pastes. The incorporation of waste gypsum into the gypsum pastes results in an acceleration of the hardening process, which might increase the volume of residues generated. This dissertation aimed to develop procedure to incorporate the gypsum residue into plaster pastes without compromising the paste mechanical properties and, especially without accelerating its hardening process. Tests have been developed to evaluate the plaster pastes setting time, consistency, workability and temperature reading in the plaster pastes in the fresh state and evaluate the hardness and axial compressive strength in the hardened state. Tests results showed the viability of the incorporation of 5% gypsum waste in substitution of gypsum in the plaster paste when combined with borax retardant additive, which promoted extension of the workable time of the paste and an increase in the pastes mechanical properties